CIVIL LIABILITY OF BANKS FOR CUSTOMER LOSSES CAUSED BY UNLAWFUL ACTS COMMITTED BY BANK EMPLOYEES: A CASE STUDY OF SUPREME COURT DECISION NUMBER 2442 K/PDT/2017 - Agustono Ariska, Jeffrey; Sukarja, Detania; Robert, Robert (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study examines the civil liability of banks in Indonesia for customer losses caused by unlawful acts committed by bank employees. Specifically, it analyzes the application of the vicarious liability principle under Article 1367 of the Civil Code and explores the legal framework governing such liability, including the Banking Law and relevant consumer protection laws. Through the case study of Supreme Court Decision Number 2442 K/Pdt/2017, the study investigates how the bank is held accountable for its employees' unlawful actions, focusing on the criteria for unlawful acts, the scope of employment, and the principle of prudence. The case establishes an important precedent regarding the proportional liability of banks in customer losses, highlighting the importance of rigorous internal controls and employee oversight. This study emphasizes the need for banks to apply the prudential principle, ensuring secure transactions and preventing fraudulent activities. The findings suggest that banks must enhance their compliance measures, such as implementing strict verification systems for large transactions, improving employee training, and fostering a culture of responsibility. Strengthening these practices will safeguard customer interests, reduce legal risks, and improve public trust in the banking sector, contributing to its long-term stability and growth.